Implications of service quality on customer loyalty in the banking sector. A survey of banks in Homabay County, Kenya - Onditi, Arvinlucy A.; Oginda, Moses N.; Ochieng, Isaac; Oso, Willis (Centre for Promoting Ideas, USA, 2012)
Marketing management research has advocated for the establishment of the determinants of customer loyalty to improve customer retention and performance. However, studies on the direct relationship between these determinants and customer loyalty have yielded inconclusive results suggesting that failure to control for contextual variables, particularly, service quality, may have confounded this relationship. In order to establish this relationship, this study used the data collected during the period of March 2012 to June 2012 from the 400 customers of the four major banks in Homabay County which included; Equity, KCB, Barclays and Cooperative Bank which have branches in major towns of the County to establish the implications of customer personality on customer loyalty determinants in banking sector in Homa Bay County, to determine the effect of service quality on customer loyalty, Descriptive statistics and multiple regression analysis were used to analyze data. The adjusted R square statistic (Adj. R2 = .046), this suggests that service quality has a significant effect on customer loyalty. Since service quality is significant predictor of customer loyalty that have not changed banks in the last two years, it was possible to build prediction model of customer loyalty using the constant and B value such that CLI = 70.024 - 0.202SQ; where CLI was the predicted customer loyalty that have not changed banks in the last three years, and SQ the status of service quality. This means that it is possible to increase customer loyalty by about 4.6% through manipulating quality of service. The study contributes to the validation of the determinants of customer loyalty. To the managers, the study shed light on the possible reasons why customer change banks more often. To the managers of public sectors offering services, the study helps in strategic change in service offering in the institutions. It is recommended that future studies focus on the effect of attitude, perception and self-concept on customer loyalty and adopt longitudinal case-study designs to establish causal relationships among variables.
Keywords: Customer loyalty; Service quality; Banks; Homa Bay County; Customer switching behavior; Consumer Behavior; consumer decision-making